1955
DOI: 10.2307/147153
|View full text |Cite
|
Sign up to set email alerts
|

Hydria-Fragments in Corinth

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The American School of Classical Studies at Athens is collaborating with JSTOR to digitize, preserve and extend access to Hesperia: The Journal of the American School of Class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The Campana collection was one of the key collections of Attic pottery (e.g. Beazley 1933; Heesen and Iozzo 2019). For example, in 1973 and 1974 Bothmer presented to MMA fragments of a cup attributed to Makron that showed in the tondo a reclining bearded banqueter playing kottabos (New York MMA inv.…”
Section: Fragmentary Cups From Old Collectionsmentioning
confidence: 99%
“…The Campana collection was one of the key collections of Attic pottery (e.g. Beazley 1933; Heesen and Iozzo 2019). For example, in 1973 and 1974 Bothmer presented to MMA fragments of a cup attributed to Makron that showed in the tondo a reclining bearded banqueter playing kottabos (New York MMA inv.…”
Section: Fragmentary Cups From Old Collectionsmentioning
confidence: 99%
“…24 Salerno PC 1812 = RVP 65, 19 = PV² 43-4 no. 58;Taplin (1993) Beazley (1952). Webster (1948) 25 suggested that the scene on the vase showing the binding of an old man resembled similar scenes in Attic comedy e.g.…”
Section: Iconographic Evidence: Comedy and Phlyax Vasesmentioning
confidence: 99%
“…18, dance is a predramatic performance, as John Davidson Beazley believed. 94 It is possible, as Ferrari states so well, that the draped Karneia dancers, like those on the Taranto and Leiden kraters, were males who took on female roles at the festival: male youths "playing girls playing stars." 95 The fifth and the seventh figures on Taranto 8263, taken together with the whirling, chiton-draped male dancers on the Trysa portal, provide compelling insight into the identity of the Motya Youth.…”
Section: Kalathiskos Dancers At the Festival Of Apollo Karneios And Ementioning
confidence: 99%